BUDAYA ORGANISASI MEMODERASI PENGARUH MOTIVASI DAN SELF-EFFICACY TERHADAP KINERJA GURU (Studi Kasus pada Guru TK di Kecamatan Bulu Kabupaten Rembang) - Sri Hartini, 13.52.02.0097; Srimindarti, Ceacilia (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to examine the effect of motivation and self-efficacy on teacher performance with organizational culture moderation. The population in this study is the early childhood teachers, in Bulu Rembang many as 103 people. Data were collected using a questionnaire, after which the data were processed using SPSS 17. Test instruments used are validity and reliability. While ui model used is the coefficient of determination and hypothesis using regression analysis. The results showed a positive and significant effect of motivation on teacher performance, self-efficacy significant negative effect on teacher performance, organizational cultural does not affect the performance, organizational cultural moderated motivation significant negative effect on teacher performance, organizational culture moderated self-efficacy significant positive effect on teacher performance. Keywords: Competence, motivation, Organizational Culture, Teacher Performance